Artificial muscle fascicles integrated with high-performance actuation properties and energy-storage function. (November 2022) - Wang, Yulian; Zhao, Yueran; Ren, Ming; Zhou, Yurong; Dong, Lizhong; Wei, Xulin; He, Jianfeng; Cui, Bo; Wang, Xiaona; Xu, Panpan; Di, Jiangtao; Li, Qingwen
Abstract: Muscle filaments are bundled together as a fascicle to generate large strength and high work capacity. However, presently developed artificial muscles are mainly investigated as single muscle filaments, which cannot meet the requirements of practical applications. Herein, an artificial muscle fascicle that was prepared by torque-balanced bundling of torsionally stable carbon nanotube muscle filaments that was prepared by an incandescent tension annealing process (ITAP) was reported. The artificial muscle fascicle exhibited excellent actuation performance with a low driving voltage (≤5.0 V), large contractile stroke (>30%), high generated isometric force (>0.5 N), and long cyclic stability (>3000 cycles). Meanwhile, artificial muscle fascicles not only can mimic the skeletal muscles to generate strength but also improve the energy-storage function many times compared to the muscle filament. Based on this excellent actuation and energy storage performances, the actuation property and energy storage functions are successfully integrated into the same artificial muscle, thereby accomplishing a multi-functional integrated device that can miniaturize their size. The multi-functionality, miniaturization, and integration of artificial muscles are essential for developing soft robots. Graphical Abstract: Borrowing the typical hierarchical structure of skeletal muscle, artificial muscle filaments are bundled together as a fascicle to generate large strength and high work capacity. We successfully integrated the actuation property and energy storage functions into the same artificial muscle, thereby accomplishing a multi-functional integrated device that can miniaturize their size. The multi-functionality, miniaturization, and integration of artificial muscles are essential for developing soft robots. ga1 Highlights: S-twist and Z-twist filaments fabricated by tensional Joule heating method with structural stability were firstly proposed. Artificial muscle fascicle for torque-balanced bundling with excellent actuation performance was firstly proposed. Artificial muscle fascicles can dramatically improve the energy storage capability. Artificial muscle fascicle integrated with actuation properties and energy-storage function into a device.